Math Problems

MathematicsPrecalculusLinear Equations → Linear Equation

Solve for the variable in the linear equation

## Questions

 $$5 - 3 y = - 2 y$$ $$- 3 a - 10 = - 7 a - 5$$ $$2 c + 7 = 3 c + 4$$ $$7 - 6 y = 3 - 10 y$$ $$- b - 1 = -5$$ $$-2 = - 5 x$$ $$1 - 2 c = 4 c - 2$$ $$6 - 5 b = 4 - 4 b$$ $$9 - 5 x = 3 - 9 x$$ $$3 - 2 a = 3 a - 3$$ $$8 - 2 y = 4 - 3 y$$ $$a + 10 = 4 - 2 a$$ $$- 4 c - 1 = - 8 c - 4$$ $$9 - 5 c = 4$$ $$a + 5 = 4$$ $$2 - 3 y = - 8 y - 1$$ $$- 4 b - 4 = - 5 b - 1$$ $$2 c + 3 = 6 c - 3$$ $$3 c - 7 = -4$$ $$5 x + 5 = 2 x + 1$$ $$6 - 4 x = 2 x + 4$$ $$c + 3 = 3 c - 2$$ $$- 2 b - 1 = - 4 b - 4$$ $$3 - 2 a = 4 a + 1$$ $$c + 9 = 4 c + 5$$ $$- 2 c - 4 = 2 c - 6$$ $$5 c - 5 = 4 c - 2$$ $$2 x - 4 = 3 x - 1$$

 $$5 - 3 y = - 2 y$$ ⇒ $$y = 5$$ $$- 3 a - 10 = - 7 a - 5$$ ⇒ $$a = \frac{5}{4}$$ $$2 c + 7 = 3 c + 4$$ ⇒ $$c = 3$$ $$7 - 6 y = 3 - 10 y$$ ⇒ $$y = -1$$ $$- b - 1 = -5$$ ⇒ $$b = 4$$ $$-2 = - 5 x$$ ⇒ $$x = \frac{2}{5}$$ $$1 - 2 c = 4 c - 2$$ ⇒ $$c = \frac{1}{2}$$ $$6 - 5 b = 4 - 4 b$$ ⇒ $$b = 2$$ $$9 - 5 x = 3 - 9 x$$ ⇒ $$x = - \frac{3}{2}$$ $$3 - 2 a = 3 a - 3$$ ⇒ $$a = \frac{6}{5}$$ $$8 - 2 y = 4 - 3 y$$ ⇒ $$y = -4$$ $$a + 10 = 4 - 2 a$$ ⇒ $$a = -2$$ $$- 4 c - 1 = - 8 c - 4$$ ⇒ $$c = - \frac{3}{4}$$ $$9 - 5 c = 4$$ ⇒ $$c = 1$$ $$a + 5 = 4$$ ⇒ $$a = -1$$ $$2 - 3 y = - 8 y - 1$$ ⇒ $$y = - \frac{3}{5}$$ $$- 4 b - 4 = - 5 b - 1$$ ⇒ $$b = 3$$ $$2 c + 3 = 6 c - 3$$ ⇒ $$c = \frac{3}{2}$$ $$3 c - 7 = -4$$ ⇒ $$c = 1$$ $$5 x + 5 = 2 x + 1$$ ⇒ $$x = - \frac{4}{3}$$ $$6 - 4 x = 2 x + 4$$ ⇒ $$x = \frac{1}{3}$$ $$c + 3 = 3 c - 2$$ ⇒ $$c = \frac{5}{2}$$ $$- 2 b - 1 = - 4 b - 4$$ ⇒ $$b = - \frac{3}{2}$$ $$3 - 2 a = 4 a + 1$$ ⇒ $$a = \frac{1}{3}$$ $$c + 9 = 4 c + 5$$ ⇒ $$c = \frac{4}{3}$$ $$- 2 c - 4 = 2 c - 6$$ ⇒ $$c = \frac{1}{2}$$ $$5 c - 5 = 4 c - 2$$ ⇒ $$c = 3$$ $$2 x - 4 = 3 x - 1$$ ⇒ $$x = -3$$